The Right to be Forgotten: an Islamic Perspective - Amr Osman (4350925) (2022)
In a landmark 1994 case, the Court of Justice of the European Union ruled that individuals had the right to ask for Internet links that contained certain information about them to be delisted by search engines. This came to be known as the “right to be forgotten.” This paper discusses the extent to which this right is consistent with the Islamic tradition. Following an overview of some aspects of the right to be forgotten and why it is endorsed in the European Union with its emphasis on privacy but not in the USA with its exaltation of free speech, the paper discusses two related issues: (1) elements in the Islamic tradition potentially conducive to endorsing a particular understanding of the right to be forgotten and (2) some possible obstacles from that tradition that could challenge the recognition of this right from an Islamic perspective. The paper concludes that despite some challenges, including Qur’anic verses and certain views, activities, and institutions, the right to be forgotten is defendable from within the Islamic tradition by reference to the principle of satr, which breaches that one should not seek to publicize personal information that causes harm to other people or even to oneself. The paper seeks to contribute to discussions on this new right by showing what a religious tradition such as Islam can offer to them. Other Information Published in: Human Rights Review License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12142-022-00672-2